Investigation of Causes of the Patient Refusal for Spinal Anesthesia - Mojgan Rahimi; Afzal shamsi; Asghar Hajipour; Mortada Jubara; Ekhlas Raheem Resen (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background aimed: Spinal anesthesia is a common technique in surgical procedures involving the injection of local anesthetic into the subarachnoid space. Patient refusal may be due to fear, negative experiences, concerns about side effects or cultural preferences, among other reasons. Failure to address these concerns can lead to anxiety, discomfort, and even cancellation of the procedure. This study aims to identify the reasons for patient refusal of spinal anesthesia. Method: This a cross-sectional study with data collected from patients who refused spinal anesthesia in two hospitals sites in Maysan-Iraq. The study included patients from different backgrounds and medical histories. The goal was to identify factors that contribute to patient refusal of spinal anesthesia, The collected data were described and analyzed using SPSS software (version 26). Result: 388 who underwent spinal anesthesia participated in this study, 255 (65.72%) accepted spinal anesthesia and 133 (34.28%) refused, the mean age was (44.12±10.86 ) years, sex was (52.32%) female and (47.68%) was male, education level, (11.08% ) had under a diploma, (66.75%) had a high school diploma, (17.53%) had a bachelor’s degree, and (4.64%) had education beyond a bachelor’s degree, prior surgery experience, (31.70%) no prior surgery experience , (68.30%) prior surgery experience, method of anesthesia for previous surgery, (15.85%)had epidural anesthesia, (45.28%) had received general anesthesia , (38.87%) had received spinal anesthesia, patient prefer pills or injection during illness, (54.52%) prefer injection, (45.48%) prefer pills, Family history of spinal anesthesia, (31.52%), had family history of spinal anesthesia, (68.48%), no family history of spinal anesthesia, source of information, (37.47%) doctor, (19.64%) friend or family, (28.94%) internet, (13.95%) television or other media. Conclusion: The study found that prior surgical experience, anesthesia method, patient preference for pills or injections, and source of information significantly influence spinal anesthesia acceptance. While, Age, sex, education level and family history may not statically significant. Further research is needed to confirm findings and identify other factors influencing patient acceptance.